Regularity of Weak Solutions to a Class of Complex Hessian Equations on Kähler Manifolds (Journal of Mathematical Study, 2021)
We prove the smoothness of weak solutions to a class of complex Hessianequations on closed Kähler manifolds, by use of the smoothing property of the corresponding gradient flow.